A Hybrid Segmentation Pattern of Partial Transmission in Computer Networks to Reduce the Complexity Level - Hameed, Rasha Subhi; Ahmed, Noora Shihab; Mahmood, Tameem Mohammed (International Journal of Integrated Engineering, 2020)
Partial transmission sequence (PTS) is seen as a related project in the framework of the Orthogonal Frequency Division ‎Multiplexing (OFDM) to suppress the medium to high Peak-to-Average Power Ratio problem. The PTS chart data is based on dividing the back into subdivisions and their weight by combining step-by-step factors. Despite the fact that PTS can reduce the high specifications. The Computational Complexity Level (CC) limits the scope of application to match PTS use with ground applications. In PTS, there are three main distribution schemes. Interleaving projects (IL-PTS), arbitrary and alternate (PR-PTS) and Ad-PTS. In this paper, another algorithm called the Hybrid Pseudo-Random and Interleaving Cosine Wave Shape ‎‎(H-PRC-PTS) is presented and the PR-PTS equilibrium is established by stabilizing the cousin waveform between languages (S-IL-C- PTS), which was suggested in the previous work. The results showed that the proposed algorithm could reduce the validity of PAPR as a PR-PTS scheme, although the CC level was significantly reduced.